Effect of room temparature (25-30C) storage of calamansi (Citrus microcarpa) on physiolochemical properties of fruit and extracted juice. - Gamelong, Glaize Anne G. (2018.)
Postharvest storage effects and damage posed challenge and losses among calamansi farmers. Because of these, several methods have been adapted to lessen total wastage. However, it is necessary to first monitor fruit quality in marketplace based on its physicochemical properties to determine the best way to prolong their shelf life. The fruit and juice of freshly picked and ripened calamansi (Citrus microcarpa) were studied for the effect of room temperature (25-30°C) storage. In line with this, physicochemical properties of the fruit and juice were studied. The fruit was examined in terms of peel color and weight loss while the juice was analyzed in terms of the volume loss, juice color, clarity, specific gravity, pH, titratable acidity, refractive index, total soluble solids and further characterization using FTIR spectroscopy. The procedures for physicochemical property analysis were adapted with modifications from several literature and works. Room temperature storage was found to have varying effects on the properties investigated. The maximum storage period was 15 days prior to the analysis. The fruit samples exhibited approximately 30% weight loss and peel color regression from green to yellow to brown. Juice color intensity had decreased, also displaying improved clearness. The juice volume decreased by 30% while specific gravity had increased. Juice pH and titratable acidity showed an inverse correlation where pH decreased as storage prolonged. Refractive index of the juice increased as well as total soluble solid content. Further characterization using FTIR, it was found that the juice had a characteristic peak at〖 1200-1500 cm〗^(-1) and was mainly composed of sugar upon comparison with IR spectra of ascorbic acid, citric acid and sucrose solution from published works.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2018.
Keywords: Calamansi -- Fruit; Calamansi -- Juice; Citrus microcarpa